2011
DOI: 10.4997/jrcpe.2011.202
|View full text |Cite
|
Sign up to set email alerts
|

Service implications of implementing guidance for oral bowel cleansing agents in colonoscopy

Abstract: Introduction:Bowel preparation has led to serious adverse events. Consequently, regulatory and advisory bodies have issued guidance, including a risk stratification of patients, aiming to minimise this risk. Aims: To determine the impact of the new guidance on our current practice of Picolax used in colonoscopy with regard to patient stratification, compliance and service implementation. Methods: Patients listed for day case colonoscopy during October 2009 were audited using data from the hospital and endoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Others have included: (1) collaboration with our renal doctors and pharmacy to change the bowel preparation protocol from exclusively use of picolax as an oral bowel cleansing agent for both flexible sigmoidoscopy and colonoscopy to a phosphate enema for the former and a polyethylene glycol-based preparation for colonoscopy5; (2) changing our method of referral to an electronic system with pathways, protocols, safety checks and bowel preparation prescription built in; (3) changing our administrative processes to include further safety checks before administration of the bowel preparation. The introduction of our new nurse practitioner-led surveillance service has been an integral part of compliance with the new surveillance category and intervals guidelines,1 2 and also has allowed compliance with the NPSA and BSG consensus guidelines for the safe use of oral bowel cleansing agents 3 4.…”
Section: Discussionmentioning
confidence: 99%
“…Others have included: (1) collaboration with our renal doctors and pharmacy to change the bowel preparation protocol from exclusively use of picolax as an oral bowel cleansing agent for both flexible sigmoidoscopy and colonoscopy to a phosphate enema for the former and a polyethylene glycol-based preparation for colonoscopy5; (2) changing our method of referral to an electronic system with pathways, protocols, safety checks and bowel preparation prescription built in; (3) changing our administrative processes to include further safety checks before administration of the bowel preparation. The introduction of our new nurse practitioner-led surveillance service has been an integral part of compliance with the new surveillance category and intervals guidelines,1 2 and also has allowed compliance with the NPSA and BSG consensus guidelines for the safe use of oral bowel cleansing agents 3 4.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus guidelines recommend a clinical evaluation, measurement of serum eGFR, and a review for the above medications and comorbidities. Based on these parameters, a recent study suggested that up to 64% of patients could be defined as “at risk” of adverse events from bowel preparation [3]. …”
Section: Introductionmentioning
confidence: 99%